Small Flock Poultry Nutrition - Michael A. Davis (EDIS, 2015)
Inadequate poultry nutrition results in substandard growth rates as well as decreased egg production and weight. In order to express the genetic potential for which they were selected, meat- and egg-type birds must receive the correct amounts of nutrients and energy through properly formulated rations. This 4-page fact sheet examines the roles of water, carbohydrates, proteins and amino acids, lipids (fats and oils), vitamins, minerals, and feed additives in poultry growth and development. It also emphasizes the importance of providing suitable feeds to birds of different ages and discusses common feeding mistakes. Written by Michael A. Davis, published by the UF Department of Animal Sciences, and reviewed and revised August 2015. This fact sheet is a major revision of “Small Poultry Flock Nutrition,” written by B. L. Damron and D. R. Sloan, April 1998. (Photo credit: Smather's Archives)